Article Review: The Disorders of Sex Development (DSD) According to the Type of Gonad Found in the Patient - Abed-Alkareem, Rand Arkan; Al Zehhawi, Dalya Jalal; Abid Alrazaq, Sura Ali (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Sexual development disorders (DSD) are categorized based on the patient's gonad type (ovary, testicle, or ovary). abnormalities of gonadal development and abnormalities of androgen synthesis or action are currently recognized etiologies and are classified as Mendelian. Sex determination and sex differentiation are the two successive stages of human sexual development. The expression of gene networks that guide the development of undifferentiated dipotent gonads into testes or ovaries is referred to as "sex determination." Throughout fetal development and adulthood, the testicles and ovaries release hormones that encourage additional gender differentiation in the body. DSD is caused by mutations found in the genes that regulate both steps. A comprehensive history, physical examination, and appropriate diagnostic testing are needed to determine the underlying etiology. Congenital abnormalities known as disorders of sex development occur when chromosomal, gonadal, or anatomic sex development is abnormal. A substantial public health burden is associated with DSD, a group of chronic medical diseases that collectively afflict approximately 1% of the population and often necessitate lifetime care from numerous experts. Certain life-threatening conditions, like adrenal crises in congenital adrenal hyperplasia, are linked to DSD. Infertility, cancer, gender dysphoria, psychosocial suffering, and widespread obstacles to health-related quality of life for patients and their families are all linked to DSD. A condition known as ambiguous genitalia occurs when it is difficult to determine a person's sex by their outward appearance. Males with ambiguous features and hypovirilization (micropenis, II absence of scrotal fusion, incomplete testicular descent, hypospadia) or females with ambiguous features and virilization (clitoromegaly, labio-scrotal fusion) are among the possible genital presentations. The family history, clinical assessment and evaluation, karyotype inquiry, imaging, and molecular testing are crucial in the workup of a newborn with ambiguous genitalia. Serum gonadotropins (LH, FSH), androgens and androgen precursors (17-hydroxypregnenolone, 17hydroxyprogesterone, androstenedione, testosterone, and dihydrotestosterone), adrenal steroids (cortisol, aldosterone, and their precursors), and Müllerian inhibiting substance (MIS) are among the detailed hormone studies that are recommended.